A STUDY OF STUDENTS’ SPEAKING SKILL THROUGH VLOG - Vina Nurviyani; Amelia Sri Rahayu (Universitas Suryakancana, 2018)
Vlog is one of the popular technology or social media which can be used as an instructional. According to Parker and Preiffer (2005) that vlog is currents video blog are essentially text blogs with externally linked videos for each entry. This research examined a study of students’ speaking skill through vlog to tenth grade of vocational high school. this research aimed to find out the implementation of learning speaking through vlog, to examine the strengths and the weaknesses of learning speaking through vlog, to investigate the responses given by students toward of learning speaking through vlog. The research was conducted in SMK Al-Fathonah Cianjur. The participant of this research was the students in tenth grade. This research used qualitative research: a study case. The research used non-participants classroom observation, interview, and questionnaire. The classroom observations were conducted three meetings. The interview and questionnaire were conducted after doing observation. Interview involved four students and questionnaire involved all students (20 students). The results showed that vlog can help them in learning speaking and foster their speaking skill. Further, the students were very enthusiastic in learning speaking through vlog. Vlog is suitable for learning speaking and narrative text material. Learning speaking through vlog is more flexible. However, students should have adequate facilities to learn speaking through vlog. Students gave positive responses of implementation learning speaking through vlog is fun, interesting and make students motivated to improve their speaking skills. Based on the findings, vlog can only be implemented in learning speaking at the intermediate and upper level such as junior high school, senior high school or vocational high school, and university.